Early retirement in Germany: Loss of income and lifetime? - Stephan Kühntopf; Thusnelda Tivig (Universität Rostock, Institut für Volkswirtschaftslehre, 2008)
The public pension system in Germany allows early retirement albeit at the cost of pension deductions. Deductions are calculated under the assumption that life expectancy is independent of the age of retirement and apply equally for men and women. The 'fair' amount of deductions is currently debated, the general feeling being that they are too low. In this paper we show that remaining lifetime and thus the perpetuity period vary with the age of retirement. In a survival analysis using micro data from the German Pension Insurance, we find that remaining life expectancy of men at age 65 receiving old-age pensions with age 60 to 66 is up to 1.9 years higher if retirement occurred later. For women, instead, life expectancy is almost independent of retirement age. Extending the analysis to invalidity pensioners (they receive pensions before the age of 60), we find that men and women reaching the age of 65 have a more than 3 years lower remaining life expectancy than old-age pensioners on average. Many other variables, like residence (West and East Germany), lifetime wage income and number of children are considered, too. In a simple model we finally calculate and compare actuarial deductions under the alternative assumptions of constant and age-of-retirement dependent life expectancy. The main conclusion is that deductions currently in law are too high for very early retirees (below age 63) and too low for all others.
Keywords: H55; J14; J26; 330; Life expectancy; retirement age; early retirement; pension deductions; Flexible Altersgrenze; Gesetzliche Rentenversicherung; Sterblichkeit; Geschlecht; Rentenfinanzierung; De